2011
DOI: 10.4269/ajtmh.2011.10-0599
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Anemia in Benin: Prevalence, Risk Factors, and Association with Low Birth Weight

Abstract: * Prevalence Ratio (PR) adjusted for malaria at the time of hemoglobin Hb assessment, body mass index (BMI), having electricity, level of education, and number of antenatal care (ANC) visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 38 publications
5
46
0
2
Order By: Relevance
“…We showed a significant reduction in the parasitic causes of anemia from the ANV1 until delivery, whereas the effect of preventive measures was less pronounced (when not unchanged) on micronutrient deficiencies. According to previous findings in industrialized 9,16,17 and developing countries, 4,10 we observed that the mean Hb decreased from late second trimester to early third trimester, whereas it increased at the end of the third trimester of pregnancy. These variations are partly because of the profound hemodynamic changes associated with pregnancy per se.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We showed a significant reduction in the parasitic causes of anemia from the ANV1 until delivery, whereas the effect of preventive measures was less pronounced (when not unchanged) on micronutrient deficiencies. According to previous findings in industrialized 9,16,17 and developing countries, 4,10 we observed that the mean Hb decreased from late second trimester to early third trimester, whereas it increased at the end of the third trimester of pregnancy. These variations are partly because of the profound hemodynamic changes associated with pregnancy per se.…”
Section: Discussionmentioning
confidence: 76%
“…3 In Benin, a previous study showed that over 60% of women experience anemia during gestation. 4 The causes of maternal anemia are complex, including infections (malaria and helminth infestations), nutrient deficiencies (iron, folic acid, and vitamin B12), and genetic factors (hemoglobinopathies). [5][6][7] In a preceding article, we had found that potentially preventable causes, such as micronutrient deficiencies and parasitic diseases, were the main factors associated with anemia in Beninese pregnant women in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly important to obtain this information at the beginning of follow-up of a pregnant woman because medications given through the ANV package (sulfadoxine-pyrimethamine IPTp, iron and folic acid, anti-helminthics) can interact with physiologic variations of hemoglobin levels during pregnancy. 4,19 Compared with previous studies, 4,10,11 use of a wide range of variables potentially influencing the hemoglobin concentration on a large number of women (more than 1,000), and few missing data enabled us to perform a powerful analysis and to deal adequately with confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Severe anemia (hemoglobin level less than 70 g/L) is present in 5-10% of the cases, and induces the most dramatic consequences, i.e., increased risk of maternal morbidity and mortality, abortion, poor intrauterine growth, preterm birth and low birth weight. 3,4 These effects in turn result in higher perinatal morbidity and mortality, and higher infant mortality rate. 5 Although the pathogenesis of anemia is multifactorial, 6,7 the disease is thought to be mainly caused by iron deficiency (ID) in developing countries and therefore, iron supplementation is routinely recommended 8 as the main prevention measure against anemia.…”
Section: Introductionmentioning
confidence: 99%
“…LBW has been associated with a large number of maternal conditions, [15][16][17][18] including malaria. Malaria is the main cause of mortality among pregnant women in Burundi and could be a factor in our setting.…”
Section: Discussionmentioning
confidence: 99%